(untitled) (Journal of Engineering, 2007)
A program of laboratory testing is carried out to study the performance of laterally loaded piles embedded in soil, which contains cavities. The testing apparatus is manufactured for carrying out the tests and a simple technique was used to simulate the cavities. The program of testing consists of five groups: Group One was carried out on pile embedded in soil without cavities. The Second and Third Groups are performed on pile embedded in soil contain single cavity located in front and in touch with pile face for the Second Group and in back and in touch with pile face for the Third one. Group Four is performed on pile with the existence of two cavities located in front and in touch with pile face. Group Five is performed on pile with the existence of three cavities located in front and at a variable distance from pile face. All tests are performed on a free head pile subjected to horizontal load. The results of this study indicate that the number of cavities and their location have a combined effect on the behavior of laterally loaded pile The effect of cavities located in front of the pile is marginal at X/D > 8 where X is the spacing between cavity and pile and D is the diameter of the pile.